Evaluating the Impact of the Primary Nursing Care Model on Nursing Outcomes: A Scoping Review - Baiq Linda Agustina; Anisah Ardiana; Muhamad Zulfatul A'la (Indonesian Journal of Global Health Research, 2025)
The Primary Nursing Care Model (PNCM) aims to enhance continuity of care, nurse autonomy, and therapeutic nurse-patient relationships. While widely implemented, its outcomes vary across settings, requiring a comprehensive assessment of its broader impact on nursing outcomes. This scoping review examines the influence of PNCM on patient care quality, nurse competence, and patient satisfaction in diverse healthcare environments. This study aims to explore and analyze the impact of PNCM on nursing outcomes, focusing on patient care quality, nurse competence, and patient satisfaction. Additionally, it seeks to identify existing research gaps and provide insights into the model’s effectiveness across different healthcare settings. A systematic search was conducted in ProQuest, ScienceDirect, and PubMed for studies published between January 2020 and December 2024. From 880 identified articles, 212 underwent full-text screening, and 15 met the final inclusion criteria based on the Joanna Briggs Institute (JBI) framework. The review focuses on studies involving nurses and patients in hospitals, outpatient clinics, and community healthcare settings where PNCM is implemented. Key outcomes assessed include patient care quality, nurse competence, and patient satisfaction. PNCM enhances nursing outcomes by strengthening nurse-patient relationships, improving competence, and fostering a safety culture. It reduces care fragmentation, increases nurse accountability, and promotes holistic care. However, research gaps persist in evaluating long-term outcomes and its application to vulnerable populations. PNCM is effective in improving nursing outcomes and patient satisfaction. Further research should explore its long-term impact and adaptation for underserved populations to optimize its benefits.